The challenges facing E-Learning in educational institutions: Case study of the Secondary Technical School (STS) - ZERHOUNI, ZOHEIR (2017)
The purpose of this research is to explore the challenges of E-Learning in the contact of the Secondary technical school (STS). The research questions the E-learning status of the UAE, the current challenges/barriers that E-learning is facing in the UAE and attempts to propose suggestions to make further progress in e-learning in the UAE. The research, thus, deploys a mixed methodology (quantitative and qualitative) to be distributed among teachers, administrative, directors, teachers and supervisors in the STS. A questionnaire was designed to explore the cultural and technical challenges facing STS E-Learning program. The questionnaire was distributed among 75 participants from whom we collected only 50 completed answers. In addition, the interview was distributed among 5 administrative personnel. The research found that the E-learning program follows a strategic philosophy which entails the spread of E-learning to all school levels. Also, E-learning philosophy encourages students to pull information to themselves to a high degree. The research also found that the directors and students are comfortably incorporating technology-based tools in their daily life. E-learning directs all resources to generate learning. The research also found that there is a technical team who helps drive the initiative and oversees its implementation and administration. Respondents’ answers gave high value for the availability of technical teams in the STS and their role in facilitating the learnability and teachability processes. The research has some limitations pertinent to the sample size which was rather small to give a generalization for the results. The research suggests implementing e-learning in an environment that is in harmony with the traditional learning so as not to dispense with the traditional, but complement each other, especially children at an early age so as not to affect other aspects such as the decline in the level of handwriting and adopting a unified Arab project to provide textbooks with electronic copies, including training programs from theoretical questions, pictures, videos and slides.